Teacher’s Engagement in the Social and Emotional Guidance ofElementary School Students - Lau, Evan; Shahren, Ahmad Zaidi Adruce; Tnay, Jessie Koh-Sing; Hiram, Ting; Chuo, Yew Ting; Mukvinder, Kaur Sandhu (Faculty of Education, Eskisehir Osmangazi University, Turki, 2020)
The present study aims to explore the criteria which motivate and prevent teachers from engaging in the social and emotional guidance of rural elementary school students in Malaysia. Face-to-face in-depth interviews were conducted with 25 teachers using purposive sampling technique and they are from 15 rural primary schools within the Sarawak state of Malaysia. While emerging themes for motivations are teachers’ task perception, colleagues’ support, students’ family support, and teachers’ professionalization, barriers include burdensome workloads and time constraints. The results are discussed to provide insights for policymakers and educational administrators on the development of a whole-school approach that aims to promote the social and emotional well being of rural students in a developing country.